Business Dispute Resolution and Its Implications for Investor Protection in Corporate Law - Wahyudi, Wahyudi; Safaat, Andi Muhammad (Sekolah Tinggi Ilmu Syariah Wal Aqidah Ash-Shofa Manonjaya, 2025)
In the business world, disputes between the parties involved are often unavoidable. Business disputes can arise due to various factors, such as differences in contract interpretation, unfair business competition, breach of agreement, or actions that are detrimental to one of the parties. Resolving business disputes is an important aspect in maintaining economic stability and business continuity, especially in the context of company law which regulates the rights and obligations of business actors, including the protection of investors. The research method used in this research is descriptive analysis, because it is based on the provisions governing business dispute resolution and its implications for investor protection in company law. The conclusion of this research is that resolving business disputes in the context of company law has a significant impact on investor protection. An effective resolution process, whether through litigation or alternative channels such as arbitration or mediation, can provide a sense of security for investors because they know there is a legal mechanism that can ensure their rights are protected in the event of a dispute. . Therefore, it is important to ensure that there are regulations that support fast and efficient dispute resolution as well as competent resolution institutions to protect investors' interests, both at the national and international levels.